Tumor-infiltrating HLA-matched CD4+ T cells retargeted against Hodgkin and Reed–Sternberg cells. (2nd June 2016) - Rengstl, Benjamin; Schmid, Frederike; Weiser, Christian; Döring, Claudia; Heinrich, Tim; Warner, Kathrin; Becker, Petra S. A.; Wistinghausen, Robin; Kameh-Var, Sima; Werling, Eva; Billmeier, Arne; Seidl, Christian; et al.
ABSTRACT: Hodgkin lymphoma (HL) presents with a unique histologic pattern. Pathognomonic Hodgkin and Reed–Sternberg (HRS) cells usually account for less than 1% of the tumor and are embedded in a reactive infiltrate mainly comprised of CD4 + T cells. HRS cells induce an immunosuppressive microenvironment and thereby escape antitumor immunity. To investigate the impact of interactions between HRS cells and T cells, we performed long-term co-culture studies that were further translated into a xenograft model. Surprisingly, we revealed a strong antitumor potential of allogeneic CD4 + T cells against HL cell lines. HRS and CD4 + T cells interact by adhesion complexes similar to immunological synapses. Tumor-cell killing was likely based on the recognition of allogeneic major histocompatibility complex class II (MHC-II) receptor, while CD4 + T cells from MHC-II compatible donors did not develop any antitumor potential in case of HL cell line L428. However, gene expression profiling (GEP) of co-cultured HRS cells as well as tumor infiltration of matched CD4 + T cells indicated cellular interactions. Moreover, matched CD4 + T cells could be activated to kill CD30 + HRS cells when redirected with a CD30-specific chimeric antigen receptor. Our work gives novel insights into the crosstalk between HRS and CD4 + T cells, suggesting the latter as potent effector cells in the adoptive cell therapy of HL.